Emotional responses, caring, self-care, and SARS-CoV-2 (COVID-19) (2021)
Currently, the pandemic caused by COVID-19 and the various measures to stop the contagion has developed multiple crises in society. The work environment has been transformed, occupational diseases have increased, therefore, it was decided to analyze the information published on the current problem and it was found that according to statistics, depressive, panic, and stress disorders have increased, due to social isolation, the change in routine and new ways of exercising job responsibilities, leading to a decrease in people’s psychological well-being. By way of conclusion, it can be said that it is important and necessary for people to develop both individual and collective resources that allow them to properly manage emotions and that integral health can be established and guaranteed.